Corrigenda of Zootaxa, 3154: 1–20 Redescriptions of three Milnesium Doyère, 1840 taxa (Tardigrada: Eutardigrada: Milnesiidae), including the nominal species for the genus - Michalczyk, Łukasz; Wełnicz, Weronika; Frohme, Marcus; Kaczmarek, Łukasz (Zootaxa, 2012)
There were major errors in three parts of the original paper (Michalczyk et al. 2012): (1) claw denotation system (lack of some square brackets), (2) diagnostic key (errors and omissions in points 8 and 12, respectively), and (3) Table 3 (minimal and maximal values swapped). In order to facilitate the use of the key and Table 3, we publish their correct versions entirely.